Immediate and Long-Term Effect of Cold Spray on Myoelectric Variables of Selected Muscles of Lower Extremity of Dominant Leg during Single-Leg Drop-Jump - Mohammad Hossein Ghasemi; Mehrdad Anbarian (Sport Sciences and Health Research)
Cryotherapy is used as an immediate effective treatment for acute sport injuries. The results of former studies about the effects of cryotherapy on myoelectric variables of muscles were slight and contradictory. The aim of the present study was to investigate immediate and long-term (20 min. later) effect of cold spray in anterior-medial area of the knee joint of dominant leg on myoelectric variables of selected muscles of lower extremity. 15 health men voluntarily participated in this study. ANOVA with repeated measures was used for data analysis. A significant decrease in semitendinosus activity (immediately and 20 min. after cryotherapy) and medialis gastrocnemius (immediately after cryotherapy) in pre-activation phase, semitendinosus (immediately after cryotherapy) in eccentric phase, as well as a significant increase in vastus medialis activity (immediately after cryotherapy) in concentric phase were observed (P<0.05). Also, a significant decrease in median frequency of tibialis anterior (immediately after cryotherapy) was observed (P<0.05). No significant differences were observed among all 3 phases of movement in co-contraction of knee joint muscles (P>0.05). It seems that the immediate effects of cold spray on the muscles activity were not severe and long-term effects were very low. In addition, since co-contraction depends on the motor control of nervous system, probably cryotherapy effects used in this study was limited to the muscles and motor program of the central nervous system has not altered. Also, it is likely that as a result of decreasing conduction velocity in muscle tissue in the concentric phase, more motor units are recruited as a compensatory mechanism. Future studies are needed to identify other changes following cryotherapy.